Exploration of ethnomathematics in the coastal areas of West Kalimantan - Dodi; Zan Zibar; Robin Saputra; Hendi Santoso; Rizqan Khairan Munandar (Ethnomath Association in cooperation with Universitas Negeri Yogyakarta, 2026)
This study explores the ethnomathematical practices of coastal communities in West Kalimantan, Indonesia, revealing how traditional knowledge systems contain rich mathematical concepts embedded in daily life activities. Utilizing qualitative methods, field observations, interviews, and documentation, the research highlights how local practices such as maritime navigation, time estimation, fishing tool construction, trade measurements, and traditional crafts reflect applied mathematics. Although these concepts are not formally expressed in academic terms, they demonstrate a deep understanding of geometry, arithmetic, estimation, and patterns. The study underscores the potential of integrating ethnomathematics into formal education to create a more contextual, inclusive, and culturally relevant mathematics curriculum. These findings support of mathematics education by recognizing and legitimizing indigenous knowledge systems as valuable learning resources. By incorporating local mathematical practices into teaching, educators can bridge the gap between abstract concepts and students’ lived experiences, fostering deeper engagement, enhancing critical thinking, and strengthening cultural identity.